STATUS PERNIKAHAN SIRI DALAM ATURAN PERUNDANG-UNDANGAN DI INDONESIA - Lutfiyah, Zeni (PARENTAL, 2013)
This research attempts to find out the form of underhand marriage committed widely in Indonesia, and also to find out how the legal status of underhand marriage is in Indonesian legislation relative to the criminal case potentially contained in such underhand practice. The research method employed was normative law research because it studies the positive law rules, using Islamic doctrine parameter, the primary means of which constituted the conceptual foundation of Islamic Law establishment, stipulation and study. More clearly, this research included in the legislation research frequently termed as law code. This research belongs to a library research exploiting the library source in the specific area related to this research, the research primary data is the law verses of Holy Qurâan and Hadist, Islam Law Compilation, and Act No.1 of 1974, and other legislation relevant to the underhand marriage. In this research, it can be found that the legality of marriage in Indonesia as mentioned in KHI when it is carried out according to Islamic law consistent with article 2 clauses 1 & 2 Act No.1 o 1974, and registered by Marriage Registration Officer (PPN). The marriage registration means the law certainty for marriage status with all consequence it results in. Meanwhile the underhand marriage is the one not registered in the authorized institution, considered as illegal according to the state provision, despite legality according to Islamic law. Thus, in underhand marriage there is an opportunity of criminal prosecution for any sexual act outside of marriage against the couple committing underhand marriage if one spouse had married other people legally.